(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of different causes of ocular injuries in patients presenting at Liaquat National Hospital, Karachi. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Liaquat National Hospital, Karachi from November 2016 to March 2018. Materials and Methods: Total 684 patients of acute ocular trauma were included. History of ocular trauma was taken. The refractive errors if existing before and usage glasses were inquired. Descriptive statistics were calculated. Stratification was done and post stratification, chi square test was applied, taken P value ≤0.05 as significant. Results: There were 489 male and 198 female patients. Mean duration was 146.92±738.24 hour. Mostly cases had either right or left eye trauma. 86.2% patients had mechanical trauma, 9.3% had chemical trauma, 1.9% had photic trauma, and 2.06% had thermal trauma. Mechanical trauma was significantly associated with age groups, eye involved, and socio economic status. Results showed significant association of chemical trauma with age group and eye involved. There was also significant association of photic trauma with gender, age groups, and education. Study found significant association of thermal trauma with eye involved and socio economic status. Conclusion: Majority of the trauma was of mechanical type presenting in young adult males in unilateral eyes.